Buffy coat volume reduction for optimization of leucapheresis harvests produced by the autoMNC program. Issue 1 (21st October 2014) - Burk, S.; Erdmann, M.; Weiss, D.; Eckstein, R.; Strasser, E. F.
<x xml:space="preserve">Abstract</x> Background and Objectives Buffy coat (BC) volume reduction was evaluated in leucapheresis (LA) harvests due to the target monocyte yield and the red blood cell (RBC) content. A packed erythrocyte volume (PEV) of 7·5 ml should not be exceeded to avoid RBC debulking with loss of leucocytes (WBCs) and the monocyte fraction during monocyte counterflow elutriation, a next step of monocyte enrichment prior to cell culture. Materials and Methods Two hundred and fifty‐three 5‐l leucaphereses (autoMNC program) performed in 102 healthy blood donors (24 female and 78 male donors) were retrospectively analysed. Different categories of BC volumes were compared due to the quality of the LA products measured by blood counts and flow cytometry. Results Collection of maximum BC volume of 10 ml and more each collection cycle (product volume: 169 ± 21 ml) resulted in 1·58 ± 0·41 × 10e9 CD14+ monocytes and high volume of packed erythrocyte (18·4 ± 8·8 ml). Low BC volume collection below 6 ml each collection cycle produced only 1·07 ± 0·40 × 10e9 CD14+ monocytes but reduced PEV significantly by 64% (6·7 ± 4·1 ml). Conclusion By reduction of the BC volume, the PEV in LA products could be reduced, which is a precondition for counterflow elutriation of monocytes. A BC volume between 7 and 8 ml per collection cycle should be adjusted to reduce PEV to 7·5 ml without relevant monocyte loss.